Programa de Avaliação de Desempenho: elementos constitutivos e pressupostos na prática avaliativa - Gomes, Ana Clotildes Colares (2010)
This study analyzes the perceptions of technical and administrative UFPA, in relation to the insertion of the components and assumptions of DBP in evaluation practice. Addresses the history, concepts, meanings, about AD methods, skills, evaluation skills, the APF and AD UFPA and Programme itself. The research is characterized as a hypothetical-deductive, descriptive and applied, using the case study. Data were analyzed using a quantitative approach, using the descriptive and inferential statistics. Data were collected through the application of questionnaires to 222 technical and administrative searched IFES, not occupants of FG and CD. The results indicate that the factors perceived in relation to the constituent elements such as: evaluation practice, measurement of competence, program management, timing, individual skills and fundamentals of the program and those related to assumptions such as: democratic process, integrative perspective, character development and pedagogical continuous evaluation practices are perceived in the evaluation process. The study concludes that comparing the results of the constituent elements and assumptions of the PAD of thechnical-administrative UFPA, it can be said about a tendency to change, though subtle, compared to the traditional model of AD, directed only to the granting of career progression for a new logic based on the results, showing an early effectiveness of the program evaluation practice by law and by the Institution. The results are confirmatory of advance evaluation practice in the institution, more so than has previously been expected, which demonstrates the value of scientific criteria of scientific research